PEMANFAATAN LIMBAH RUMAH TANGGA SEBAGAI MEDIA PEMBELAJARAN GREEN EDUCATION DI SISWA KELAS V SEKOLAH DASAR NEGERI LENGKONG WETAN 1 KOTA TANGERANG SELATAN - Firmansyah, Riski; Patriasurya Azhar, Arry; Yenni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of implementing Green Education in elementary schools as an effort to foster environmental awareness from an early age. One form of implementation is through the use of household waste as a learning medium that supports the teaching and learning process, while increasing students' awareness in maintaining environmental sustainability. This study aims to describe the use of household waste as a learning medium based on Green Education for fifth-grade students at SDN Lengkong Wetan 1, South Tangerang City. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation involving teachers and fifth-grade students. The research procedure was carried out through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that household waste, both organic and inorganic, has been effectively utilized as a learning medium. Various types of waste such as plastic bottles, cardboard, straws, and eggshells are processed into media and works that support learning activities. The use of these media can increase activeness, creativity, interest in learning, and environmental awareness. Although there are still obstacles in waste management and limited time for implementation, the use of household waste as a learning medium based on Green Education has been implemented well and has made a positive contribution in forming an environmentally conscious character in students. The findings of this study indicate that household waste can be a learning medium that supports Green Education and forms an environmentally conscious character.